An evaluation of two small group learning strategies among third-year medical students at the Faculty of Medicine, Siriraj Hospital, Mahidol University - Kunatip Sutthiyuth (2022)
Small group learning (SGL) is a discussion-based teaching strategy that can improve critical thinking, analytical skills, problemsolving, and interpersonal skills. This study aimed to evaluate student satisfaction in two SGL models among third-year medical students enrolled in a blood and lymphoid systems II course at the Faculty of Medicine Siriraj Hospital, Mahidol University in Bangkok, Thailand. A total of 318 students were divided into 12 groups, and each group had one facilitator. All included students and groups were exposed to both the central summary (CS) model and the individual facilitator summary (IFS) model (both SGLs). A questionnaire was developed to evaluate student rating of learning activities, perceived benefit, timing, workload, and satisfaction. Medical students rated the IFS model superior to the CS model for four of five parameters [confidence in performing and interpreting a laboratory test (83.6% vs. 78.8%), guidance for self-learning (52% vs. 39.5%), increased understanding of a disease (87.7% vs. 72.1%), and application of knowledge (77.4% vs. 70.2%), respectively]. Moreover, the IFS model was rated as having more suitable timing and workload and better satisfaction than the CS model. The results of this study suggest a strong preference for the IFS model over the CS model among medical students. hematology; medical education research; medicine; small group; undergraduate